Фунтик и трое с большой дороги: [сказка : для младшего школьного возраста] / Валерий Шульжик - Шульжик Валерий Владимирович (Дрофа, 2005)
Экземпляры: ДО (04.03.2010) / Инвентарный номер: 44919 / Цена: 50.00 / Авт.знак: Ш 95 / ГРНТИ: 17.82.93 / ББК: 84 (2Рос=Рус)6